1991
DOI: 10.1136/adc.66.9.1075
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation in cystic fibrosis.

Abstract: The availability of non-invasive oxygen satur-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…We found that SpO 2 levels progressively diminished as pulmonary function (FEV 1 ) decreased, a finding that has been already described by other authors [ 37 , 38 ]. Therefore, in our study the higher levels of SpO 2 reached during glycine administration probably were reflecting the improvement of respiratory function.…”
Section: Discussionsupporting
confidence: 89%
“…We found that SpO 2 levels progressively diminished as pulmonary function (FEV 1 ) decreased, a finding that has been already described by other authors [ 37 , 38 ]. Therefore, in our study the higher levels of SpO 2 reached during glycine administration probably were reflecting the improvement of respiratory function.…”
Section: Discussionsupporting
confidence: 89%